THE NEED FOR MAINTENANCE OF PEOPLE IN BUSINESS LIMA - Barrón Aráoz, Ampelio Ricardo (2014)
Maintaining people is the health, safety and quality of work life issues that have been addressed in the research project 2013. Occupational hygiene is related to environmental conditions which guarantee the physical and mental health, also with the welfare conditions of the people. From the point of view of physical health, the site of labor constitutes the action area of occupational hy-giene and involves aspects related to the human body exposure to external agents such as noise, air, tempe-rature, humidity, lighting and equipment working. From the point of view of mental health, the work environment must establish healthy psychological and sociological conditions that act positively on the behavior of individuals, to avoid effects such as emotional stress. The term quality of work life (QWL) was coined by Louis Davis in the 1970s when developing a project on design fees. This reference does Peter Drucker in his book “Management Challenges in the XXI century”.